Contribution to the knowledge of Aculeata сhymenoptea) of łódzkie voivodeship - Kowalczyk, Jan; Szczepko, Katarzyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2008)
The paper presents new distribution records of 135 species of nine families of Aculeata (Chrysididae, Scoliidae, Tiphiidae, Mutillidae, Sapygidae, Eumenidae, Vespidae, Sphecidae) in łódzkie voivodeship.